Female authorship in anglo-canadian literature: from pioneers to postmodernists - Romero, Lis Doreto [UNESP]; Rapucci, Cleide Antonia [UNESP] (Universidade Estadual de Maringa, 2024)
Canadian literature, or CanLit, has a distinct history. The immigrant women who went to the New Land, then a British colony, and had literary aspirations, were quick to wield their pens: they produced works, although not without difficulty, which initially had their literary characteristics overlooked. In later years, these pioneers had their works revisited and used as a source of inspiration for 20th-century female authors who aimed to subvert and transgress norms. Thus, through the lens of feminist criticism, which aims to analyze the content of women's productions and highlight authors who received little or no recognition, this article aims to present a selection of Canadian women authors from the pioneers to the postmodernists and establish meaningful connections between their works. This connection considers the metafictional aspects of postmodern productions in which a return to the past is seen as a desire for transformation. Furthermore, this article also aims to bring Canadian culture closer to the Brazilian audience, as research on the literature produced by Canadian women is limited in Brazilian academia.
Autoria feminina na literatura anglo-canadense: das pioneiras às pós-modernistas
Keywords: Canada; canlit; female authorship; feminist criticism